Molecular characterization of mucopolysaccharidosis type IVA patients in the Andean region of Colombia. Issue 3 (20th September 2021) - Pachajoa, Harry; Acosta, Maria Amparo; Alméciga‐Díaz, Carlos J.; Ariza, Yoseth; Diaz‐Ordoñez, Lorena; Caicedo‐Herrera, Gabriela; Cuartas, Daniel; Nastasi‐Catanese, Jose Antonio; Ramírez‐Montaño, Diana; Silva, Yiseth Katherine; Moreno, Lina; Satizabal, Jose; et al.
Abstract: Colombia has a high prevalence of mucopolysaccharidosis (MPS) type IVA. Nevertheless, data regarding the mutation spectrum for MPS IVA in this population have not been completely characterized. Forty‐seven families and 53 patients from seven different Colombian regions were tested for MPS IVA mutations. We compared the sequences with the N ‐acetylgalactosamine‐6‐sulfatase (GALNS) reference sequence NM_000512.4, and gene variants were reported. Bioinformatics analysis was performed using SWISS‐MODEL. The mutant proteins were generated by homology from the wild‐type GALNS 4FDJ template obtained from the PDB database, and visualization was performed using Swiss‐PDBViewer and UCSF Chimera. The predictive analysis was run using different bioinformatic tools, and the deleterious annotation of genetic variants was performed using a neural network. We found that 79% and 21% of the cohort was homozygous and compound heterozygous, respectively. The most frequent mutation observed was p.Gly301Cys (78.3% of alleles), followed by p.Arg386Cys (10.4% of alleles). A novel mutation (p.Phe72Ile) was described and classified in silico as a pathogenic variant. This study reveals the mutation spectrum of MPS IVA in Colombia. The high prevalence of the p.Gly301Cys mutation suggests a founder effect of this variant in the Colombian population that causes diseases in the Andean region (via migration). These data can facilitate genetic counseling, prenatal diagnosis, and the design of therapeutic interventions.